Assessing copepod (Crustacea: Copepoda) species richness at different spatial scales in northwestern Romanian caves - Ioana N. Meleg; Frank Fiers; Oana Moldovan (Subterranean Biology, 2011)
The aim of the present study was to assess copepod species richness in groundwater habitats from the Pădurea Craiului Mountains, Transylvania (northwestern Romania). Five species richness estimators (one asymptotic, based on species accumulation curves, and four non-parametric) were compared by testing their performances in estimating copepod species richness at three hierarchical spatial scales: cave, hydrographic basin, and karstic massif. Both epigean and hypogean species were taken in account. Two data sets were used in computing copepod species richness: 1. samples collected continuously during one year (dripping water) and seven months (pools) from five caves, and 2. samples collected from pools in twelve additional caves (data gathered from literature). Differences in copepod species richness among caves and hydrographic basins suggest that local environmental features are important in determining local species richness trends.